Islamic Corporate Governance Index, foreign investment and firm's performance of Shar'iah Compliance Companies: a comparative study of Indonesia and Malaysia / Hilwani Hariri, Roshima Said and Takiah Mohd. Iskandar - Hariri, Hilwani; Said, Roshima; Mohd. Iskandar, Takiah (Research Management Institute (RMI), 2013)
Corporate governance has been a pertinent issue for more than two decades. The regulators in Malaysia have actively participated in addressing issues in corporate governance as observed in the changes that have taken place since the first introduction of the Malaysian Code of Corporate Governance in year 2000 to the Corporate Governance Blueprint 2011. The concept of governance in Islam is highlighted and eventually a checklist on Islamic corporate governance is developed. The checklist is useful to aid governance practice of companies that are categorized as 'Shari'ah' compliance companies in the Bursa Malaysia. This paper firstly, introduces the dimension of Islamic Corporate Governance Index (ICGI). Secondly it determines the relationship of ICGI to performance with ICGI dimensions from previous literature and content analysis. The relationship was tested on the Shar'iah Compliance Companies in Malaysia and Indonesia for the year 2009. The results found that there are significant difference between Shar 'iah Compliance Companies in Malaysia and Indonesia. The total ICGI also does not influence the performance.